Elevated Plasma Cardiac Troponin T Levels Caused by Skeletal Muscle Damage in Pompe Disease. (February 2016) - Wens, Stephan C.A.; Schaaf, Gerben J.; Michels, Michelle; Kruijshaar, Michelle E.; van Gestel, Tom J.M.; in 't Groen, Stijn; Pijnenburg, Joon; Dekkers, Dick H.W.; Demmers, Jeroen A.A.; Verdijk, Lex B.; Brusse, Esther; van Schaik, Ron H.N.; et al.
Abstract : Background—: Elevated plasma cardiac troponin T (cTnT) levels in patients with neuromuscular disorders may erroneously lead to the diagnosis of acute myocardial infarction or myocardial injury. Methods and Results—: In 122 patients with Pompe disease, the relationship between cTnT, cardiac troponin I, creatine kinase (CK), CK-myocardial band levels, and skeletal muscle damage was assessed. ECG and echocardiography were used to evaluate possible cardiac disease. Patients were divided into classic infantile, childhood-onset, and adult-onset patients. cTnT levels were elevated in 82% of patients (median 27 ng/L, normal values <14 ng/L). Cardiac troponin I levels were normal in all patients, whereas CK-myocardial band levels were increased in 59% of patients. cTnT levels correlated with CK levels in all 3 subgroups ( P <0.001). None of the abnormal ECGs recorded in 21 patients were indicative of acute myocardial infarction, and there were no differences in cTnT levels between patients with and without (n=90) abnormalities on ECG (median 28 ng/L in both groups). The median left ventricular mass index measured with echocardiography was normal in all the 3 subgroups. cTnT mRNA expression in skeletal muscle was not detectable in controls but was strongly induced in patients with Pompe disease. cTnT protein was identified by mass spectrometry in patient-derived skeletal muscle tissue. Conclusions—: Elevated plasma cTnT levels in patients with Pompe disease are associated with skeletal muscle damage, rather than acute myocardial injury. Increased cTnT levels in Pompe disease and likely other neuromuscular disorders should be interpreted with caution to avoid unnecessary cardiac interventions. Abstract : Supplemental Digital Content is available in the text.